LEGAL BASIS OF FARM OPERATIONS - Daminov Khusniddin Absalomovich (Modern American Journals, 2025)
The article analyzes the legal foundations of the activities of farms, their essence on the basis of the Law of the Republic of Uzbekistan "On Farming" and a number of regulatory legal acts. The opinions of researchers are also studied.
Keywords: Agriculture, entrepreneurial activity, farming, multidisciplinary farming, statistical information.